The first woman philosopher: love to the lyric wisdom - Santoro, Fernando (Revista Archai, 2019)
Sappho’s Tithonius poem can be considered a presocratic philosophical text? Some characteristics make us see those verses in its philosophical mood: 1) It portrays a situation of loving learning, love (philía) to knowledge; 2) It provides a general and essential statement on humanity: “No being that is human can escape old age.” 3) It makes a critique of the common sense’s idea of humanity, and explains why corruption of becoming is more decisive than mortality; 4) It provides an attitude and a practical wisdom disrupted by a fundamental question, as “What can I do?”, 5) There is a particular term (maybe a concept?) to lead and give unity of his philosophical school or system of thought.